Friend or Foe: MicroRNAs in the p53 network. (10th April 2018) - Luo, Zhenghua; Cui, Ri; Tili, Esmerina; Croce, Carlo
Abstract: The critical tumor suppressor gene TP53 is either lost or mutated in more than half of human cancers. As an important transcriptional regulator, p53 modulates the expression of many microRNAs. While wild-type p53 uses microRNAs to suppress cancer development, microRNAs that are activated by gain-of-function mutant p53 confer oncogenic properties. On the other hand, the expression of p53 is tightly controlled by a fine-tune machinery including microRNAs. MicroRNAs can target the TP53 gene directly or other factors in the p53 network so that expression and function of either the wild-type or the mutant forms of p53 is downregulated. Therefore, depending on the wild-type or mutant p53 context, microRNAs contribute substantially to suppress or exacerbate tumor development.